Adaptive mechanism of submergence tolerance by Sub1 A - Suwetha, S; Gnanamalar, R P; Elamathi, S; Mary, P C N; Arulmozhi, R; Dhandapani, M; Subrahmaniyan, K; Shanmugam, A; Pushpa, R (Plant Science Today, 2025)
Among the various abiotic stresses affecting the growth, development, and yield of rice, submergence caused by continuous flooding without adequate drainage poses a significant threat. This stress is particularly detrimental in lowland areas with poor drainage, often near coastal regions, where excessive rainfall leads to prolonged waterlogging. Continuous waterlogging during germination severely impacts the germination of directly seeded rice crops, while seedling establishment suffers post-transplantation due to seedling decay and mortality. Submergence tolerance is an adaptive physiological and biochemical mechanism that has evolved in indica rice, enabling the plant to cope with the effects of anaerobic conditions caused by prolonged submergence. The putative progenitor Oryza rufipogon is well adapted to marshy environments. This study discusses the mechanisms of introgression of anaerobic germination and submergence tolerance from O. rufipogon through molecular analysis of genomic regions. It also explains the physiological and biochemical mechanisms that influence anaerobic germination and submergence tolerance. Lowland areas characterized by flooding due to excessive rainfall and inadequate drainage, particularly near coastal regions, require anaerobic germination and submergence tolerance for rice cultivation. Identifying new sources of submergence tolerance beyond the Sub1 gene, followed by genomic structural characterization for the development of pre-breeding genetic sources, is essential. Additionally, well-characterized quantitative trait loci (QTLs) and genes that confer submergence tolerance need to be transferred precisely.